A Comprehensive Meta-analysis on Intra Ocular Pressure and Central Corneal Thickness in Healthy Children - Majid FARVARDIN; Fatemeh HEIDARY; Kourosh SAYEHMIRI; Reza GHAREBAGHI; Mahmoud JABBARVAND BEHROOZ (Tehran University of Medical Sciences, 2017)
Background: Glaucoma is the major ophthalmic public health issue and a leading basis of blindness. Elevated intraocular pressure (IOP) is still a foremost risk factor in development and progression of glaucoma. Central corneal thickness (CCT) may play as the risk factor for the progression of glaucoma, closely associated with IOP especially in pediatric age group. This study performed a pioneering investigation combining the outcomes of multiple studies using a meta-analytic approach. Methods: Nineteen published articles between 1980 and 2015 were designated by searching Scopus, PubMed, and Google Scholar and analyzed with random effects model while I² statistics employed to find out heterogeneity. Subsequently, the information statistically analyzed by Stata software ver. 11.20. Results: The mean IOP has been documented to 16.22 mmHg (95% CI: 15.48-16.97) in all races subgroups. Analyzing the data by race-based subgroups revealed the lowest IOP of 12.02 mmHg (95% CI: 11.40-12.64) in Indian children while IOP of 17.38 mmHg (95% CI: 15.77-18.98) documented in black children as the highest measurement. The mean CCT was 553.69 micrometer (95% CI: 551.60-555.78) among all races. Lowest CCT of 536.60 mm (95% CI: 531.82-541.38) has been documented in mixed Malay-Indian children whereas Chinese children ought to the highest CCT value of 557.68 mm (95% CI: 553.10-562.25). Conclusion: Findings of published studies were inconsistent when considered independently; however, meta-analysis of these results showed a significant correlation between CCT and IOP. Owing to non-uniform methods used to measure IOP and CCT in studies, data were stratified into various subgroups according to the instruments used to measure IOP and CCT.